2014
DOI: 10.1371/journal.pone.0088247
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Postural Control Reduces Sit-to-Stand-to-Sit Performance in Individuals with Chronic Obstructive Pulmonary Disease

Abstract: BackgroundFunctional activities, such as the sit-to-stand-to-sit (STSTS) task, are often impaired in individuals with chronic obstructive pulmonary disease (COPD). The STSTS task places a high demand on the postural control system, which has been shown to be impaired in individuals with COPD. It remains unknown whether postural control deficits contribute to the decreased STSTS performance in individuals with COPD.MethodsCenter of pressure displacement was determined in 18 individuals with COPD and 18 age/gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 41 publications
2
36
0
3
Order By: Relevance
“…Beauchamp et al demonstrated that the test could discriminate fallers from non-fallers; the test 246 duration was 3.1 seconds longer in fallers compared with non-fallers 30 . Moreover, longer time to complete the TUG test at baseline and after 1-year follow-up period were 248 predictors of deterioration in disease related health status 33 .Sit-to-stand test: Fifteen studies which used the STS test to evaluate lower limb functionality were found7,18,19,[21][22][23][35][36][37][38][39][40][41][42][43] . The protocols vary greatly(Table 1), including differences in chair height, which ranged from 40 to 48 cm7,22,[35][36][37][38][39][40][41][42] or was adjusted to…”
mentioning
confidence: 99%
“…Beauchamp et al demonstrated that the test could discriminate fallers from non-fallers; the test 246 duration was 3.1 seconds longer in fallers compared with non-fallers 30 . Moreover, longer time to complete the TUG test at baseline and after 1-year follow-up period were 248 predictors of deterioration in disease related health status 33 .Sit-to-stand test: Fifteen studies which used the STS test to evaluate lower limb functionality were found7,18,19,[21][22][23][35][36][37][38][39][40][41][42][43] . The protocols vary greatly(Table 1), including differences in chair height, which ranged from 40 to 48 cm7,22,[35][36][37][38][39][40][41][42] or was adjusted to…”
mentioning
confidence: 99%
“…The present study induced significant changes in center of pressure behavior, showing that postural change (sitting‐to‐orthostatic position) can increase postural instability. According to other studies, the sit‐to‐stand maneuver impairs postural control in individuals with chronic obstructive pulmonary disease . In addition, lower balance tests scores are associated with BP falls during postural challenge in older adults with orthostatic hypotension .…”
Section: Discussionmentioning
confidence: 88%
“…However, some older individuals have an impaired respiratory pattern, such as in chronic obstructive pulmonary disease, so that ventilatory contributions to postural balance compensation can be more pronounced . Furthermore, chronic obstructive pulmonary disease patients have impaired postural control from sit‐to‐stand‐to‐sit performance, requiring more time to stand up and sit down in a chair …”
Section: Introductionmentioning
confidence: 99%
“…One practice trial is necessary [78,79]. With normative values for the elderly established [78,79], individuals with COPD generally take 21-46 % longer to perform the test [39,80].…”
Section: Five Repetition Sit-to-stand Test (5sts)mentioning
confidence: 99%